Mating Call, Dog Whistle, Trigger: Asymmetric Alignments, Race, and the Use of Reactionary Religious Rhetoric in American Politics. (March 2023) - Perry, Samuel L.
Asymmetric social alignments are transforming American partisan rhetoric, particularly how politicians leverage identity-based appeals. For example, asymmetric religious, racial, and ideological alignments within the Republican party now make reactionary religious rhetoric increasingly strategic. Focusing on that case, I propose a novel conceptual model to understand what such rhetoric aims to accomplish. Reactionary religious rhetoric advertises, appeals, and activates on a spectrum from overt to subconscious registers, which I explain using three metaphors: mating call, dog whistle, and trigger. Within a context of asymmetrical partisan "sorting, " Christian nationalist rhetoric overtly advertises partisanship (mating call). Rhetoric deploying encoded terms like "Christian" and "socialist" appeals to ethno-culture, connecting specific political opponents to abstract ethno-religious threats (dog whistle). Lastly, research on overlapping identities increasingly suggests rhetoric involving threats to "Christianity" may unconsciously activate White racial threat (trigger). I consider applications of this conceptual model to growing political appeals to nationalist and populist identities.